Comparative application analysis and test verification on equivalent modeling theories of honeycomb sandwich panels for satellite solar arrays. (19th October 2020) - Wang, Wei; Luo, Haitao; Fu, Jia; Wang, Haochen; Yu, Changshuai; Liu, Guangming; Wei, Qiming; Wu, Shufan
Due to the difficulty of direct finite-element modeling for honeycomb sandwich panels, it is more common to apply equivalent modeling theories. It is necessary to compare their equivalent precision and then to determine the method with the best equivalent performance so as to prepare for the application in satellite solar arrays. The first 10 natural frequencies are obtained by analyzing the dynamic characteristics of sandwich panel theory model, honeycomb panel theory model, and equivalent panel theory model. The equivalent errors of different equivalent methods are obtained by comparison with the analysis results of real honeycomb panel model. Then, the sandwich panel theory and the Hoff theory with high precision are used to simulate the solar array panel. The two methods are further verified and compared by simulation and experiment. Finally, the sandwich panel theory with the highest accuracy is selected to simulate the vibration response of the solar array panel based on the above work. By comparing the frequency response analysis results with the test results, it is found that the maximum acceleration response error is within 7%, and the corresponding frequency error of the main direction is within 3%. The comparison between random analysis results and test results shows that the root mean square response errors of acceleration in three directions are within 13.7%. It is proved that the sandwich panel theory has high accuracy in the honeycomb structure. Based on the background of a specific space project, this study innovatively applies the test results to compare several typical equivalent theories of honeycomb sandwich panels so as to get a theory with the highest equivalent precision. The final conclusion has been applied to the design of related space products and proved to be feasible. This provides important reference and basis for the structural design of the satellite.